Mycoplasma pneumoniae Clinical Manifestations, Microbiology, and Immunology - Takashi Shimizu (Frontiers Research Topics, 2017)
Mycoplasma pneumoniae (Mp) is a major human pathogen that causes both upper and lower respiratory infections, and is one of the leading causes of community acquired pneumonia (CAP), accounting for 11-15% of CAP throughout the world. Additionally it is known to induce an inflammatory process which depends on several mechanisms such as virulence of Mp (lipoproteins, community acquired respiratory distress syndrome (CARDS) toxin, oxidative products) and host defenses (cellular immunity and humoral immunity). Although it is a common pathogen, the pathogenesis for Mp infections is not yet fully understood. From the clinical point of view, since the pioneer studies in the 1960s and 1970s on the clinical presentation of Mp associated disease, the diagnostics approaches have changed dramatically leading to a better understanding of the clinical presentation and new issues have emerged - such as antibiotics resistance. The purpose of this Frontiers ebook is to thoroughly review and discuss the clinical presentation in view of the improved diagnostics, microbiological and immunological analysis of Mp infections, with focus on the history of Mp, clinical features of disease, bacterial structure of Mp and mechanism of gliding, clinical and laboratory diagnostics, the role of lipoproteins and Toll-like receptor, CARDS toxin, subtyping of Mp isolates and genome analysis, macrolide resistance and treatment.